Dinâmica populacional de insetos fitófagos e predadores em cana-de-açúcar sob aplicação de silício - Otuka, Alessandra Karina [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The use of silicon (Si) is a technique that increases plant resistance to insect pests. Also, it contributes significantly to the reduction of feeding activity and damage caused by these arthropods. This study evaluated the effect of Si application in two varieties of sugarcane on phytophagous and predators species of insects. The study aimed to verify the influence of this mineral on the abundance and diversity of species, analyze the population fluctuation of predominant species and their relationship with meteorological factors, and to identify the relationship between phytophagous and predator insects. Sugarcane varieties used were IAC-SP 963060 and IAC-SP 962042 and Si source used was calcium silicate and magnesium at a dose of 2.0 t ha-1. Sampling was performed every two weeks from February 2012 to January 2014. It was observed that the Si in varieties of sugarcane causes jaws wear of Atta sexdens (Linnaeus, 1758), it increases the incidence of Doru luteipes (Scudder, 1876) and Darditilla sp. and it decreases populations Gryllus spp. and Melanaphis sacchari (Zehntner, 1897). Application of Si does not change ants' diversity, but it reduces Mutillidae's and Staphylinidae's. The Si in sugarcane raises the population peaks of A. sexdens, Brachymyrmex sp., D. luteipes, Mahanarva fimbriolata (Stal, 1854). Sthetorus sp., Pheidole oxyops Forel, 1908, Scarites sp. 1 and Euborellia sp. are the predators most often associated to phytophagous insects in sugarcane. The maximum ambient temperature influences negatively D. luteipes and M. fimbriolata populations and minimum temperature does the same to Abaris basistriata Chaudoir, 1873, and Scarites sp. 1 populations. Increased rainfall reduces Syntermes sp. and Gryllus assimilis (Fabricius, 1775) populations

A utilização de silício (Si) constitui em uma técnica que incrementa a resistência de plantas a insetos-praga, contribuindo significativamente para a redução da atividade alimentar e dos danos ocasionados por esses artrópodes. Neste trabalho avaliou-se o efeito da aplicação de Si sobre espécies de insetos fitófagos e predadores em duas variedades de cana-de-açúcar. O estudo teve por objetivos verificar a influência desse mineral sobre a abundância e diversidade de espécies, analisar a flutuação populacional de espécies predominantes e a relação destes com fatores meteorológicos, além de verificar a relação entre insetos fitófagos e predadores. As variedades utilizadas foram IAC-SP 963060 e IAC-SP 962042 e a fonte de Si aplicado foi o silicato de cálcio e magnésio na dose de 2,0 t.ha-1. A amostragem foi realizada quinzenalmente a partir de fevereiro de 2012 a janeiro de 2014. Verificou-se que o Si nas variedades de cana-de-açúcar provoca desgaste nos dentes mandibulares de Atta sexdens (Linnaeus, 1758), aumenta a ocorrência de Doru luteipes (Scudder, 1876) e Darditilla sp. e diminui as populações de Gryllus sp. e Melanaphis sacchari (Zehntner, 1897). A diversidade de formigas não se altera com a aplicação de Si, mas a de Mutillidae e Staphylinidae é reduzida. O Si em cana-de-açúcar eleva os picos populacionais de A. sexdens, Brachymyrmex sp., D. luteipes, Mahanarva fimbriolata (Stal, 1854). Sthetorus sp., Pheidole oxyops Forel, 1908, Scarites sp. 1 e Euborellia sp. são os insetos predadores mais frequentemente associados aos insetos fitófagos em cana-de-açúcar. A temperatura máxima do ambiente influencia negativamente as populações de D. luteipes e M. fimbriolata e a temperatura mínima as populações de Abaris basistriata Chaudooir, 1873 e Scarites sp. 1. O aumento da precipitação pluvial reduz as populações de Syntermes sp. e Gryllus assimilis (Fabricius, 1775)
Keywords: Cana-de-açúcar; Pragas agricolas; Inseto - População; Biodiversidade; Plantas - Resistência aos insetos; Plants Insect resistance